Cross-reactive humoral immune responses against seasonal human coronaviruses in COVID-19 patients with different disease severities. (October 2021) - Imai, Kazuo; Matsuoka, Masaru; Tabata, Sakiko; Kitagawa, Yutaro; Nagura-Ikeda, Mayu; Kubota, Katsumi; Fukada, Ai; Takada, Tomohito; Sato, Momoko; Noguchi, Sakiko; Takeuchi, Shinichi; Arakawa, Noriaki; et al.
Highlights: ELISAs were used to evaluate cross-reactive antibody responses against other HCoVs in COVID-19 patients IgG antibodies for HCoVs did not differ between severe and mild cases on admission HCoV-HKU1 and -OC43 IgG-S levels were higher in severe cases during convalescence Abstract: Background: The cross-reactive antibody response against seasonal human coronaviruses (HCoVs) was evaluated according to disease severity in patients with COVID-19 in Japan. Methods: In total, 194 paired serum samples collected from 97 patients with COVID-19 (mild, 35; severe, 62) were analyzed on admission and during convalescence. IgG antibodies against the nucleocapsid (N) and spike (S) proteins of SARS-CoV-2 and four seasonal HCoVs (HCoV-NL63, -229E, -OC43, and -HKU1) were detected by enzyme-linked immunosorbent assays. Results: There was no difference in optical density (OD) values for seasonal HCoVs on admission between the severe and mild cases. In addition, a specific pattern of disease severity-associated OD values for HCoVs was not identified. Significant increases in OD values from admission to convalescence for HCoV-HKU1and -OC43 IgG-S, and for HCoV-NL63 and -229E IgG-N were observed in the severe cases. Significant differences were observed between the mild and severe cases for HCoV-HKU1 and -OC43 IgG-S OD values during convalescence. Correlations were found between the fold changes for HCoV-OC43 IgG-S OD values, and for SARS-CoV-2 IgG-S OD values, and C-reactive protein, lactate dehydrogenase, and lymphocyte levels. Conclusion: There was no association between the antibody titer for seasonal HCoVs in the early phase of COVID-19 and disease severity.